Risk Factors of Maternal Mortality in Calabar - P. Akpabio, Uduakobong; Angioha, Pius U.; Egwuonwu, Chiamaka V.; Awusa, Esther B.; Ndiyo, Magareth N. (JINAV: Journal of Information and Visualization, 2020)
Maternal mortality remains unacceptably high despite both local and international programs carried at reducing the incidence. Nigeria suffers from 800 maternal death per 100,000 births. This study examines the extent to which cultural practices and quality of medical care determines maternal mortality in Calabar, Cross River State. Using the survey research design, data were collected from 400 women aged between 15 and 49 from Calabar using a self-developed structured questionnaire. The participants were selected using cluster and purposive sampling technique. Data collected from the field was analyzed using descriptive statistics and regression analyses at 0.05 confidence level. Result from the analysis revealed that uncivilized cultural practices lead to high maternal mortality. 75.64 per cent of the participant reported cases of complications during birth in the hands of traditional birth attendants. cultural practices account for 49 per cent of the variation in maternal mortality. Also, result revealed that poor care delivery or quality of medical care leads to high maternal mortality. 54.14 per cent of the participants reported that the cost of medical care for a pregnant woman in the hospital is too expensive. 69.43 per cent reported there have been deaths as a result of lack of care in hospitals. Based on these findings There is need for the government and its health ministry to increase the number of primary health centres in the nation as well as strengthen this health centres to collect high-quality data to respond to the needs and priority of women and girls amongst others.